2007
DOI: 10.1017/s0007123407000257
|View full text |Cite
|
Sign up to set email alerts
|

European Opinion About Immigration: The Role of Identities, Interests and Information

Abstract: This article assesses the influence of material interests and cultural identities on European opinion about immigration. Analysis of respondents in twenty countries sampled in the 2002–03 European Social Survey demonstrates that they are unenthusiastic about high levels of immigration and typically overestimate the actual number of immigrants living in their country. At the individual level, cultural and national identity, economic interests and the level of information about immigration are all important pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
745
4
28

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 838 publications
(813 citation statements)
references
References 6 publications
36
745
4
28
Order By: Relevance
“…Indeed, recent European studies have presented mixed evidence for propositions of static group conflict theory. Some studies confirm that the size of the foreign population (Quillian, 1995;Scheepers et al, 2002;Semyonov et al, 2008;Schneider, 2008) or GDP-based income statistics (Quillian, 1995, Schneider, 2008 have an impact on outgroup attitudes, while others were not able to replicate these findings (Sides and Citrin, 2007;Strabac and Listhaug, 2008). These contradictions might be due to differences in concrete operationalizations of the variables, but also to problems with the cross-cultural comparability of the measurements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, recent European studies have presented mixed evidence for propositions of static group conflict theory. Some studies confirm that the size of the foreign population (Quillian, 1995;Scheepers et al, 2002;Semyonov et al, 2008;Schneider, 2008) or GDP-based income statistics (Quillian, 1995, Schneider, 2008 have an impact on outgroup attitudes, while others were not able to replicate these findings (Sides and Citrin, 2007;Strabac and Listhaug, 2008). These contradictions might be due to differences in concrete operationalizations of the variables, but also to problems with the cross-cultural comparability of the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…With measurements from 'only' 17 countries and three time points, the sample size at the highest level is too small for the asymptotic properties of the multilevel estimators to kick in (for similar arguments, see: Coenders and Scheepers, 2008;Sides and Citrin, 2007). For this reason, we prefer to use a two-step approach.…”
Section: Table 2 About Herementioning
confidence: 99%
See 2 more Smart Citations
“…Drawing Migration and multiculturalism 27 on this seminal work, value-based threats have regularly been shown to be associated with anti-immigrant prejudice (McLaren, 2003;Sides & Citrin, 2007). For example, a study conducted in the Netherlands showed that perceived symbolic, but not material, threat predicted prejudice against Muslim immigrants (Velasco Gonzáles, Verkuyten, Weesie, & Poppe, 2008).…”
Section: Threatening the Values Of The National Ingroupmentioning
confidence: 99%